Comparative Proteomic and Morphological Change Analyses of Staphylococcus aureus During Resuscitation From Prolonged Freezing - Suo, Biao; Yang, Hua; Wang, Yuexia; Lv, Haipeng; Li, Zhen; Xu, Chao; Ai, Zhilu (Frontiers in Microbiology, 2018)
When frozen, Staphylococcus aureus survives in a sublethally injured state. However, S. aureus can recover at a suitable temperature, which poses a threat to food safety. To elucidate the resuscitation mechanism of freezing survived S. aureus, we used cells stored at -18°C for 90 d as controls. After resuscitating the survived cells at 37°C, the viable cell numbers were determined on tryptic soy agar with 0.6% yeast extract (TSAYE), and the non-injured-cell numbers were determined on TSAYE supplemented with 10% NaCl. The results showed that the total viable cell number did not increase within the first 3 h of resuscitation, but the osmotic regulation ability of freezing survived cells gradually recovered to the level of healthy cells, which was evidenced by the lack of difference between the two samples seen by differential cell enumeration. Scanning electron microscopy (SEM) showed that, compared to late exponential stage cells, some frozen survived cells underwent splitting and cell lysis due to deep distortion and membrane rupture. Transmission electron microscopy (TEM) showed that, in most of the frozen survived cells, the nucleoids (low electronic density area) were loose, and the cytoplasmic matrices (high electronic density area) were sparse. Additionally, a gap was seen to form between the cytoplasmic membranes and the cell walls in the frozen survived cells. The morphological changes were restored when the survived cells were resuscitated at 37°C. We also analysed the differential proteome after resuscitation using non-labelled high performance liquid chromatography–mass spectrometry (HPLC-MS). The results showed that, compared with freezing survived S. aureus cells, the cells resuscitated for 1 h had 45 upregulated and 73 downregulated proteins. The differentially expressed proteins were functionally categorized by Gene Ontology enrichment, KEGG pathway and STRING analyses. Cell membrane synthesis-related proteins, oxidative stress resistance-related proteins, metabolism-related proteins, and virulence factors exhibited distinct expression patterns during resuscitation. These findings have implications in the understanding of the resuscitation mechanism of freezing survived S. aureus, which may facilitate the development of novel technologies for improved detection and control of foodborne pathogens in frozen food.